SU11274 suppresses proliferation and motility of pancreatic cancer cells - TOMIZAWA, MINORU (Oncol Lett, 2015)
Mesenchymal-epithelial transition factor (c-Met) is associated with the proliferation and motility of cancer cells. c-Met expression has been detected in surgical pancreatic cancer specimens, and its overexpression is associated with a poor prognosis. SU11274 is a specific inhibitor of c-Met. In the present study, the cell proliferation and motility of pancreatic cancer cells treated with SU11274 was investigated. The PANC-1, MIA-Paca2, NOR-P1, PK-45H, PK-1 and PK-59 pancreatic cancer cell lines were used. The expression of c-Met and cyclin D1 was analyzed by quantitative polymerase chain reaction. In addition, a 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium inner salt assay was performed to assess cell proliferation, and a scratch assay was performed to assess cell motility. c-Met expression was higher in PANC-1, PK-45H, PK-1 and PK-59 cell lines compared with that in normal pancreatic tissue. Following treatment with 30 µM SU11274, the proliferation of MIA-Paca2 and PK-45H cells was suppressed to 19.8±10.7% (P<0.05) and 45.8±14.8% (P<0.05) of the control level, respectively. Furthermore, cyclin D1 expression was downregulated to 43.7±17.9% (P<0.05) and 53.2±18.6% (P<0.05) of the control level in the MIA-Paca2 and PK-45H cell lines, respectively, following treatment with 30 µM SU11274. In addition, cell motility was reduced to 1.0±0.3% in MIA-Paca2 (P<0.05) and 14.7±3.5% in PK-45H (P<0.05) following treatment with 30 µM SU11274, compared with the motility of untreated cells. These results indicated that SU11274 suppresses the proliferation of pancreatic cancer cells via the downregulation of cyclin D1. The present study also demonstrated that cell motility was suppressed by treatment with SU11274.